(untitled) - Pearce, Douglas G. (Wallingford, Oxfordshire, 2012)
Frameworks are the foundation of good scholarship. They structure, organize and communicate research, underpin individual studies and shape the field of study as a whole. This book introduces students to the concept of frameworks in tourism research and provides a review, discussion and critique of frameworks. Theoretical, conceptual, analytical and integrative frameworks are all covered in detail, with the features, use, strengths and limitations of each form discussed and illustrated using a wide range of examples and applications across the field of tourism studies.
Keywords: Tourism,Du lịch; Research,Nghiên cứu